Abdel Rahman Bin Al-Mansour Nick Named “Shanjoul” And His Role In Al-Amereyah State (Journal of Namibian Studies : History Politics Culture, 2024)
Al-Amereyah State was established in Andalusia by the hand of Al-Mansour Mohammad BinAbi Amer in the reign of the Ommayad Caliph Al-Hakam Al-Mustanser (302-366H/ 915-978 A.D.). The Ninth among Bani Omayah Emir in Andalusia, who entrusted all his affairs to Al-Mansour, who afterwards was nick-named “The Triumphant Chamberlain”, his son Abdel Malek shared him in building the state till he was died in the year (399H./ 1008 A.D.). And followed him in concealment of the Caliph Hisham, the supported his brother Abdel Rahman, Nick-named (Shanjoul). He was with a changeable personality and “Filled so much of the cup of pleasures until the heeltap”. He was repudiated shameless. And inspite of his shamelessness, he thought to become the Caliph after the Ommayad Caliph Hisham the supported by the Al-Mighty God. He enchanted on that and informed the caliph with that, insisted and threatened the caliph with killing. Then he prepared his famous decree to take over caliphate, collected all people to be witnesses and called upon the caliph to be present with the public, and read the wording of the decree that he had prepared earlier, and asked the caliph to sign it; wording him to be heir to the throne after the caliph. The caliph optionally signed that at the presence of the public and the distinguished figures, celebrations were performed by his companions and servants from the Barbarians. The Ommayads were angry and rebelled against him. At that time he was preparing for a new invasion against the Christians, he was deceived and arrogant does not accept advice for non-invasion. He was advised and feared of the public confusion, but he was careless, self-deceived and got out in a rainy day with chilly cold and went for invasion. During that he was informed that Mohammad Bin Hisham Bin Abdel Jabbar Bin Abdel Rahman Al-Naser attacked the city of Al-Zaherah, occupied and destroyed it. He became at his wit’s end and confused. He turned returning to Cortopa careless with advices that were addressed to him from close and intimate people. Suddenly all people scattered from about him, because of his shamelessness and immorality. So he was shiftless and remained alone. Mohammad Bin Hisham asked him to enter his obedience, but he refused and the matter terminated in his killing and Al-Amereyah state in Andalusia was removed. His father Al-Mansour established it and enlarged its concerns and he came to destroy it by his pleasures and shamelessness. It is really saying the truth corresponding the Al-Mighty God’s saying in the Holy Qura’n “Extracts the Alive from the Dead and extracts the Dead from the Alive”. He is a man who lost a Kingdom running and seeking behind pleasures, shamelessness, arrogance and immorality.